DAMPAK POLA ASUH TOXIC PARENTS TERHADAP KESEHATAN MENTAL DALAM PERKEMBANGAN KEMAMPUAN EMOSIONAL ANAK USIA DINI - Tria Nurjanah, Eka; Yeni Rachmawati (LPPM IAD Probolinggo, 2024)
This research is motivated by parenting patterns, because parents are someone who has an important role in the family, especially in good parenting patterns for the development of children to become better individuals in living their lives. The application of parenting patterns has a very important role in child development, but there are still many parents who have unknowingly made mistakes in providing parenting patterns for their children, one of which is toxic parenting patterns, toxic parents have a very big negative effect on children. If this toxic parenting pattern continues, it will have a very fatal effect on children's mental health, especially the development of children's emotional abilities which are disturbed and will affect children's lives in their daily lives. Thus, this study aims to analyze the impact of mental health obtained by early childhood, especially in the development of early childhood emotional abilities due to the application of Toxic Parents parenting patterns. This study uses a literature review method. This study is expected to be a reference for parents to better understand how to provide the best parenting patterns for children. Keywords: Toxic Parents, Mental Health, Children's Emotional Abilities